(untitled) (GYMNASIUM, 2008)
Our project proposes a correlation among physical education aims, based on european union politics in our science area, contents and didactic strategies of teaching-learning made in a curricular vision, with different treatment strategies of evaluation that can mark out the pupil’s knowledge and skills, his advancement and, behavior, centering evaluation on practical side. It is obvious that there are appreciated the results, too that can’t be quantified measured with accuracy: the attitudes, the behaviors, the capacities, all this being valuable objectives in the educative process. This research will be supported by the participative action research paradigm. This type of research has the advantage that it starts from real life generated questions, being confused, for a moment, with the daily activities realized by any teacher in the didactical process. the action research has another advantage and that is the determination of the stimulation. in physical education there can be used in system all evaluation forms, by using evaluation strategies specific to this activities.